The Influential Bonds of Womanness in Greta Gerwig’s Barbie - Kartiningsih, Rindrah; Rengganis, Dewi Ayu; Pasopati, Rommel Utungga; Wijaya, Kusuma; Hariyono, Hariyono (Alphabet, 2024)
Greta Gerwig's 2023 movie Barbie offers a compelling exploration of the bonds of womanness within a fictional matriarchal society. This journal examines how these bonds are portrayed in the movie, analyzing their influence on the characters and narrative. By focusing on the concept of feminist sisterhood as stated by Bell Hooks, the paper explores how the movie’s depiction of solidarity and mutual support among women reflects and contributes to feminist discourse. Through qualitative method and explorative approach, the analysis considers how the bonds of womanness in Barbie Land not only shape the characters' experiences but also serve as a commentary on real-world gender dynamics. In conclusion, womanness shapes such influential bonds of shared experience and achievements among women, especially in the movie of Barbie.